Intensifying Zakat Al-Fitr Payment with Rice Instead of Money: Aiming for Sustainable Socio-economic Growth - Alim, Muhammad Nurul (International Journal of Zakat, 2023)
This study aims to analyze the economic opportunities of paying zakat al-fitr with rice instead of money. As known, the school of Maliki, Shafi’i and Hanbali states that zakat al-fitr can only be paid in the form of staple foods for the local community, in contrast to Imam Hanafi who allows zakat al-fitr with money. This study applies an exploratory method. The results show that based on the rice supply chain, zakat al-fitr with rice creates economic opportunity namely potential of zakat al-fitr rice procurement, rice supply chain added value, selling special package of zakat al-fitr rice, farm worker empowerment, engagement of supply chain support, application of salam contracts and collection of zakat on agricultural products. These results imply that loss of economic opportunities occurs when Muslims pay zakat al-fitr with money instead of rice. This study recommends that paying zakat with staple food can enhance the sustainable socio-economic growth of the ummah.